PENGENALAN LITERASI MEDIA REALIA HERBARIUM DAN TERARIUM BERBASIS KERAGAMAN TUMBUHAN HUTAN TROPIS PADA GURU KELAS AWAL DI SDN 016 TARAKAN - Fadhlan Muchlas Abrori; Aidil Adhani; Fitri Wijarini; Darius Rupa; Agustina Dai Pain (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2021)
Abstract: The teaching and learning process in school needs to emphasize the contextual aspect to know the relation between material and life around. One of the media that can be used is herbarium and terrarium. This program provides understanding and training of herbarium and terrarium-making techniques to teachers to be used in the learning process in the classroom, especially in the early classes. This program's result includes: the average of plant identification skill's teacher before the program was 34.5 and after implementation of the program was 85.4. Based on the result of the ability of teacher of making herbarium, the highest score on the aspect of